Respiratory Carcinogenesis - Pokorski, Mieczyslaw; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The book blends basic and clinical research on respiratory carcinogensis. The contributions tackle a variety of respiratory-related cancers, notably non-small cell lung carcinoma, pleural mesothelioma, mediastinal tumors, or larynx cancer. The focus is on the search for novel molecular markers, derived from easily accessible tissues in clinical settings, such as the serum or bronchoalveolar lavage fluid, which could help diagnose cancer at an early stage and have a prognostic therapeutic value. The transcriptional mechanisms which endow cells with the capacity for unlimited proliferation are considered, with silencing of tumor suppressor genes is the exemplar. Chapters provide insight into a variety of cancer-related disorders of the respiratory tract, novel ways of differential diagnosis and treatment. The aim is to bring the current clinical procedures into alignment with the latest basic research findings. The book is a text for respiratory researchers, clinicians, and pathologists.
The Role of Mediastinoscopy in the Diagnosis of Thoracic disease: One-Year Single Center Experience, M. Chabowski, A. Szymanska-Chabowska, J. Skotarczak, D. Janczak Jr, L. Pawlowski, and D. Janczak -- Shoulder Ring Complaints as a Rare First Symptom of Malignant Pleural Mesothelioma, J. Lorkowski, O. Grzegorowska, A. Kotela, W. Weryński, and I. Kotela -- Primary Prosthetic Voice Rehabilitation in Patients after Laryngectomy: Applications and Pitfalls, V. Calkovsky and A. Hajtman -- A Unilateral Hemothorax as a Presenting Manifestation of Mediastinal Spindle Cell Sarcoma, M. Chabowski, A. Szymanska-Chabowska, M. Szolkowska, and D. Janczak -- Diagnostic Performance of Different Pleural Fluid Biomarkers in Tuberculous Pleurisy, J. Klimiuk, R. Krenke, A. Safianowska, P. Korczynski, and R. Chazan -- Low-Dose Computer Tomography as a Screening Tool for Lung Cancer in a High Risk Population -- A. Nahorecki, M. Chabowski, T. Kuźniar, B. Kędzierski, P. Jaźwiec, A. Szuba, and D. Janczak -- Decreased FAM107A Expression in Patients with Non-Small Cell Lung Cancer, D. Pastuszak-Lewandoska, K.H. Czarnecka, M. Migdalska-Sęk, E. Nawrot, D. Domańska, J. Kiszałkiewicz, J. Kordiak, A. Antczak, P. Górski, and E. Brzeziańska-Lasota -- Clinical Significance of HMGB-1 and TGF-β Level in Serum and BALF of Advanced Non-Small Cell Lung Cancer, K. Jakubowska, W. Naumnik, W. Niklińska, and E. Chyczewska -- TGF-β and SMADs mRNA Expression in Pulmonary Sarcoidosis -- W.J. Piotrowski, J. Kiszałkiewicz, D. Pastuszak-Lewandoska, A. Antczak, P. Górski , M. Migdalska-Sęk, W. Górski, K. Czarnecka, E. Nawrot, D. Domańska, E. Brzeziańska-Lasota.
Keywords: Cancer research; Respiratory organs—Diseases.; Cytokines; Growth factors; Cancer Research; Pneumology/Respiratory System; Cytokines and Growth Factors